1995
DOI: 10.1006/viro.1995.1542
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the Major Vaccinia Virus Envelope Antigen

Abstract: The major envelope antigen of vaccinia virus is an acylated protein of M(r) 37,000 (p37K) which is required for the formation of extracellular enveloped virions (EEV). Despite its important role in the wrapping process, p37K has not been studied in much detail. In order to better characterize this protein we have undertaken a detailed biochemical analysis. Sodium carbonate treatment showed that p37K is tightly bound to the viral envelope. Its resistance to proteinase K digestion indicates that it is not expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
56
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 0 publications
4
56
0
Order By: Relevance
“…EEV has been shown to be important in long-distance spread of infectious virus in vitro and in vivo, and is also relevant in terms of pathogenicity (Payne, 1980). P37 is the major protein in the external envelope of EEV (Hiller & Weber, 1985 ;Payne, 1978), and is tightly bound to the inner surface of the outer membrane (Roos et al, 1996 ;Schmutz et al, 1995). Within infected cells, P37 is localized in the Golgi region, associated with vesicles which form doublewalled envelopes around IMV (Hiller & Weber, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EEV has been shown to be important in long-distance spread of infectious virus in vitro and in vivo, and is also relevant in terms of pathogenicity (Payne, 1980). P37 is the major protein in the external envelope of EEV (Hiller & Weber, 1985 ;Payne, 1978), and is tightly bound to the inner surface of the outer membrane (Roos et al, 1996 ;Schmutz et al, 1995). Within infected cells, P37 is localized in the Golgi region, associated with vesicles which form doublewalled envelopes around IMV (Hiller & Weber, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is an acylated protein (Child & Hruby, 1992) and it has been recently shown that cysteine residues at positions 185 and 186 are both modified by palmitate (Grosenbach et al, 1997). The palmitate moiety is responsible for the hydrophobic nature of the protein (Grosenbach et al, 1997 ;Schmutz et al, 1995), mediates its membrane interaction and therefore directs its correct intracellular location. Palmitylation is crucial for function, since non-palmitylated versions of the protein, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The B5R product is a 42-kDa type I integral membrane component of the EEV (8,23). The F13L ORF encodes a nonglycosylated, palmitylated protein that is the most abundant component of the EEV membrane (15,16,18,19,40). The F13L protein contains a variant of the HKD (His-Lys-Asp) motif that is conserved in a superfamily of phospholipases and phospholipid synthases (25,33,45) and has been reported previously to exhibit broad-specificity lipase activities in vitro (1).…”
mentioning
confidence: 99%
“…Proteins encoded by seven viral genes have been identified as specific components of IEV, CEV, or EEV membranes. Five of these, A33R, A34R, A36R, A56R, and B5R, are glycoproteins, whereas F12L and F13L are unglycosylated (11,13,28,40,42,48,54,64,72). Recent studies indicated that the A36R protein is present only in the outer IEV membrane, which is not retained on extracellular virions (64).…”
mentioning
confidence: 99%
“…The resistance of EEV-associated F13L protein to protease digestion suggested that it was present on the inner surface of the EEV envelope (54). In infected cells, the F13L protein was localized on trans-Golgi and IEV membranes (25,53).…”
mentioning
confidence: 99%